Maths, Class 03, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745100 2129771:XWZGW9EE 4752638:ML6TGJVZ
Keywords: SSEIP